A Batch Feeder for Inhomogeneous Bulk Materials; IOP Conference Series: Materials Science and Engineering; Vol. 124 : Mechanical Engineering, Automation and Control Systems (MEACS2015) - Vislov I. S.; Kladiev S. N. Sergey Nikolaevich; Slobodyan S. M. Stepan Mikhaylovich; Bogdan A. M. Anna Mikhailovna (Integrated Computer Control Systems in Mechanical Engineering, 2016)
Title screen